Mechanisms of Diffusion for Conditional Cash Transfer Programs in Latin America. The Chilean Case - Osorio Gonnet, Cecilia (Íconos)
Conditional Cash Transfer Programs (CCT) spread across Latin America beginning in the mid-1990s. By 2010, 17 countries in the region had implemented some sort of CCT program. The academic literature identifies diverse mechanisms of diffusion to understand the logic behind the process, however more disussion is still required about the various aspects of the diffusion process and how to treat them in empirical analysis. This article attempts to identify the characteristics and the operationalization of the various difussion mechanisms of the CCT program: emulation, learning and coercion. These aspects are analyzed through a qualitative case study of the formulation of Chile’s CTT program, Chile Solidario. The conclusions consider the contribution of this proposal and discuss the future challenges in analyzing difussion processes that help us to understand broader changes in public policies in the region.